The impact of atorvastatin on hemorheology and inflammatory cytokines of patients with hypertensive nephropathy - WANG Li; ZHOU Guan-yan (Linchuang shenzangbing zazhi)
Objective To explore the effects of atorvastatin triple regimen on serum inflammatory factors and hemorheology in patients with hypertensive nephropathy. Methods 134 patients with hypertensive nephropathy from March 2014 to February 2015 in the Department of Nephrology in Yingshan County People’s Hospital were enrolled in this study and numbered by admission time,and then randomly divided into the observation group( n = 67) and the control group( n = 67) according to the odd or even number. The control group was treated with amlodipine(2. 5 mg,1 time/day,taken after meals) and valsartan(80 mg,1 time/day,taken at meals or on an empty stomach),and the observation group was treated with the triple regimen of atorvastatin( 20 mg,1 time/day,taken before bed-time),amlodipine( 2. 5 mg,1 time/day,taken after meals) and valsartan(80 mg,1 time/day,taken at meal or empty stomach). After 3 months of treatment,the renal function,inflammatory factors,hemodynamics,adverse reactions and other indicators were compared between the two groups. Results After 3 months of treatment,the levels of urinary albumin(Alb),serum creatinine(SCr) and blood urea nitrogen(BUN) in the observation group were significantly lower than those in the control group( P < 0. 05). The levels of serum procalcitonin,C-reactive protein and erythrocyte sedimentation were significantly lower in the observation group than those in the control group( P< 0. 01). The levels of high blood viscosity,low shear whole blood viscosity and plasma viscosity were significantly lower I nthe observation group than those in the control group( P < 0. 05). There were no significant differences in nausea,vomiting and headache between the two groups(10. 45% vs. 8. 96%)( x~2=0. 085,P > 0. 05). Conclusions Atorvastatin triple regimen is helpful in protecting renal function in patients with hypertensive nephropathy,which may be related to decreases in serum levels of inflammatory factors and improvements in hemorheology.